A space mission to detect imminent Earth impactors. (5th March 2015) - Valsecchi, G. B.; Perozzi, E.; Rossi, A.
Abstract : One of the goals of NEO surveys is to discover Earth impactors before they hit. How much warning time is desirable depends on the size of the impactors: for the larger ones more time is needed to mount effective mitigation measures. Initially, NEO surveys were aimed at large impactors, that can have significant global effects; however, their typical time scale is orders of magnitude larger than human lifetime. At the other extreme, monthly and annual events, liberating energies of the order of 1 to 10 kilotons, are immaterial as a threat to mankind, not justifying substantial expenditure on them. Intermediate events are of more concern: in the megatons range, timescales are of the order of centuries, and the damage can be substantial. A classical example is the Tunguska event, in which a body with a diameter of about 30 to 50 m liberated about 5 megatons in the atmosphere, devastating 2 000 square kilometers of Siberian forest.